(untitled) (Orfeu, 2019)
This text focuses on questions related to fundaments for the chamber musician and chamber music teacher’s work. The little attention music performance scholars have been given to the fundaments of its practice and teaching, has caused many uninformed instructions throughout chamber musicians’ education. The main goal of the present paper is to discuss the theme as well as to offer directions to both chamber music students and teachers. Based on the concepts Musical Performance (Ray, 2015a) and Musical Performance Pedagogy (Ray, 2015b), this article presents fundaments and suggestions on how to organize an undergraduate chamber musiccourse. The text is organized in three main parts: 1) Fundamental approaches to chamber music didactics; 2 Practice and didacts of chamber music elements; and 3) Considerations on how to plan a chamber music course. The discussions and suggestions here presented showed clearly that there are benefits of the conceptual studies addressed to chamber music students and teachers, particularly those involved in formal educational.